UP Diliman Shopping Center level of patronage of UPD Faculty and staff based on urban form attributes - Orbon, Glenn T. (2013)
The University Shopping Center (SC) of the University of the Philippines Diliman serves as the commercial core of the campus providing several services that cater to the needs of the UP Community. This study show the different urban form attributes that affect the level of patronage of faculty and staff members of the University such as (1) distance of proximity of the academic units, (2) availability of local public transport system, and (3) responsiveness of the commercial center. Other off-campus amenities near UP Diliman also emerged as secondary options in availing the needs and services of the UP employees.
Keywords: University of the Philippines (Diliman). Shopping Center